PERANAN KUALITAS SISTEM e-REGISTRATION TERHADAP KEPUASAN PENGGUNA DAN KEPATUHAN WAJIB PAJAK DI KANTOR PELAYANAN PAJAK (KPP) PRATAMA CIMAHI - Syafariani, Fenny; Nadeak, Ronauli (JURNAL GAUNG INFORMATIKA, 2012)
This research was conducted as background by the using of e-Registration system that aims to enhance customer satisfaction and service manager registrationTaxpayer Identification Number (TIN) to the target in order to achieve compliance with the taxpayer. This study aims to determine how much the quality of e-Registrationsystem is instrumental to the satisfaction of the management and taxpayer compliance. The method used is inferential statistical method with quantitative approachthe data analysis using statistical tools used to analyze the variables studied. The data used are the primary data using questionnaires. The subject of this study weremanagers who specialize in handling and use of taxpayers e-Registration system at KPP Pratama Cimahi. From the analysis of these things can be explained as follows: of the t test results are known hypothesis H0: Ï = 0, the hypothesis H0 :